2017
DOI: 10.7196/sajch.2017.v11i3.1246
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the severity of motor impairment in children with cerebral palsy seen in Enugu, Nigeria

Abstract: Cerebral palsy (CP) is a neurodevelopmental disability. It is the most common cause of physical disability in childhood and occurs worldwide with a prevalence of 2-2.5 per 1 000 live births in the Western world. [1] The prevalence of CP in Nigeria is unknown and the rate of children attending neurology clinics in Nigeria varies broadly from 16% to 50.3%. [2-4] The University of Nigeria Teaching Hospital (UNTH), Enugu, reported CP to be the second most frequent neurological disorder seen in the paediatric neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Indeed, Iloeje and Ogoke [64] in their study on severity of CP in children found a strong correlation between postnatal CNS infections and severe/non-ambulatory CP. Thus the greater contribution of postnatal CNS infections to CP causation in LMICs may in part be the reason for the relatively poorer gross motor function in children with CP from LMICs compared to their counterparts from HICs [64].…”
Section: Meningitis/meningoencephalitis Cerebral Malaria and Cpmentioning
confidence: 95%
See 2 more Smart Citations
“…Indeed, Iloeje and Ogoke [64] in their study on severity of CP in children found a strong correlation between postnatal CNS infections and severe/non-ambulatory CP. Thus the greater contribution of postnatal CNS infections to CP causation in LMICs may in part be the reason for the relatively poorer gross motor function in children with CP from LMICs compared to their counterparts from HICs [64].…”
Section: Meningitis/meningoencephalitis Cerebral Malaria and Cpmentioning
confidence: 95%
“…In a word, regardless of either vascular obstruction from sequestration of parasitized red blood cells in brain capillaries and venules or cytokine-mediated inflammatory injury, ultimately, cerebral malaria causes grey and white matter damage. Severe spastic bilateral CP specifically spastic quadriplegia is the expected long-term correlate of these postnatal CNS infections since they are diffuse processes with extensive brain damage [64]. Indeed, Iloeje and Ogoke [64] in their study on severity of CP in children found a strong correlation between postnatal CNS infections and severe/non-ambulatory CP.…”
Section: Meningitis/meningoencephalitis Cerebral Malaria and Cpmentioning
confidence: 97%
See 1 more Smart Citation
“…Iloeje and Ogoke [29] in 2017 reported that the type of CP (physiology and topography), etiological factors and the number of accompanying impairments (supplemental disorders) were positively associated with the severity of gross motor dysfunction and walking ability of children with CP. In that study [29], children with spastic quadriplegic type, bacterial meningitis as etiological factor or many (five or six) accompanying impairments all had severe gross motor dysfunction and were non-ambulatory. Therefore, the other classifications may suggest functional abilities in children with CP.…”
Section: Functional Classificationmentioning
confidence: 99%
“…El trastorno motor en pacientes con PCI no viene solo, suele acompañarse de alteraciones cognitivas, de lenguaje, sensoriales, y de conducta, así como problemas musculo esqueléticos y epilepsia (4,5) . El trabajo multidisciplinario es obligatorio en estos niños, por su condición neurológica y múltiples comorbilidades, e incluye equipos de pediatras, neuropediatras, traumatólogos, terapistas físicos, ocupacionales y de lenguaje (1) .…”
Section: Introductionunclassified